Selection of investment company based on interval neutrosophic vague heronian operator - Hashim, Hazwani; Awang, Noor Azzah; Mohamad, Siti Nurul Fitriah (Academica Press Solutions, 2022)
An investment decision is important for a large company to maintain continuous profit. Investment in large-scale projects must consider various factors such as risk index, growth index and the social-political impact index. The investment problem is challenging due to the presence of multiple criteria, decision-makers, and alternatives. The investment decision-making environment is a situation characterised by inconsistency and uncertainty. To deal with these problems, aggregation operator (AO) and set theory play a vital role. Aggregation operators are an important component in decision-making problems involving multiple criteria and multiple decision-makers. Heronian Mean (HM) is an effective AO that can consider the interrelationship among different input arguments. Meanwhile, the interval neutrosophic vague set (INVS) is effective in handling uncertainty and inconsistency information in decision-making problems. Therefore, the combination of HM and INVS namely interval neutrosophic vague Heronian Mean (INVHM) operator is more appropriate when ranking the best company to invest in. The algorithm of decision-making procedure is developed using the proposed INVHM operator to solve the investment decision problems. In addition, the sensitivity analysis is performed with respect to the different parameters of and . The findings show that the ranking order is sensitive to the value of parameters used. Thus, the proposed INVHM operator is a reliable and effective AO in decision-making problems. The comparative analysis is performed with some existing operators to validate the effectiveness of the proposed INVHM operator.